Inovasi Teknologi Tepat Guna: Pengembangan Ecosmart Oyster sebagai Alat Pembuka Tiram Ramah Lingkungan - Rifda Nur Hikmahwati Arif; Sintia Salam; Nabila Nasir; Melda Longde'; Salma Samputri (JKM: Jurnal Kemitraan Masyarakat, 2025)
The conventional process of opening oyster shells using manual knives has various limitations, including low work efficiency, high risk of worker injury, and damage to oyster meat integrity that impacts the economic value of the product. This development activity aims to design and implement an appropriate technology-based oyster opener that is efficient, safe, and sustainable. The implementation method adopts a Research and Development approach through five systematic stages: needs analysis through literature study and field observation; design based on ergonomic principles and lever mechanics; prototype fabrication using local teak wood and mild steel materials; technical performance testing; and evaluation and design finalization. The Ecosmart Oyster prototype was designed applying first-class lever principles with load-fulcrum-force configuration that produces a mechanical advantage of 3.5. Testing results on 50 oyster samples showed significant improvements in opening time efficiency of 50 percent with an average duration of 15 seconds per unit, reduction of meat damage up to 70 percent with 90 percent producing intact high-quality products, and zero work injury incidents during the testing process. This tool offers an innovative solution that increases the productivity of local oyster processors, minimizes occupational safety risks, and supports the sustainability of the fisheries industry through the use of environmentally friendly materials.